2021
DOI: 10.3390/nu13061865
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium Glutamate Induces Changes in Hepatic and Renal Metabolic Profiles and Gut Microbiome of Wistar Rats

Abstract: The short- and long-term consumption of monosodium glutamate (MSG) increases urinary pH but the effects on the metabolic pathways in the liver, kidney and the gut microbiota remain unknown. To address this issue, we investigated adult male Wistar rats allocated to receive drinking water with or without 1 g% MSG for 2 weeks (n = 10, each). We performed a Nuclear Magnetic Resonance (NMR) spectroscopy-based metabolomic study of the jejunum, liver, and kidneys, while faecal samples were collected for bacterial DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In our study, with increasing duration of the experimental period, we observed progressive edema, replacement of pancreatic parenchyma with connective and adipose tissues, and deviations in the histological structure of the acini in the pancreatic gland. Our findings are consistent with other studies where obesity in animals was induced by high-fat diets, resulting in pancreatic steatosis, inflammation, and fibrosis [1,7,9,10]. Thus, the experimental modeling of sodium glutamate and subsequent investigation of the structure of the pancreatic gland allowed us to identify the main pathomorphological changes.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, with increasing duration of the experimental period, we observed progressive edema, replacement of pancreatic parenchyma with connective and adipose tissues, and deviations in the histological structure of the acini in the pancreatic gland. Our findings are consistent with other studies where obesity in animals was induced by high-fat diets, resulting in pancreatic steatosis, inflammation, and fibrosis [1,7,9,10]. Thus, the experimental modeling of sodium glutamate and subsequent investigation of the structure of the pancreatic gland allowed us to identify the main pathomorphological changes.…”
Section: Discussionsupporting
confidence: 91%
“…Although less attention has been paid to the dietary additives captured in the NOVA classification, volumes of pre-clinical research have linked the non-nutritive components of foods (e.g., emulsifiers, flavor enhancers, and artificial colors) to non-communicable diseases, including gastrointestinal and mental disorders [143][144][145][146][147][148][149][150]. In animal models, various dietary additives, including emulsifiers and monosodium glutamate (MSG), have been shown to alter the gastrointestinal microbiome [151][152][153][154]; ultra-processed food-induced alterations to the gut microbiome might account for many of the diet's health-related consequences [155] (Figure 2). Indeed, compared to either MSG or a high-fat diet alone, the combination of MSG and a high-fat diet (i.e., characteristic of ultra-processed foods) has been noted to cause a shift in gut microbiota reflective of an obesity signature [156].…”
Section: Wide-ranging Health Effects: From Excitotoxins To Mental Healthmentioning
confidence: 99%
“…Some taste enhancers are chemical substances, such as monosodium glutamate (MSG) and hydrolyzed protein (Israr et al, 2016). Since the use of monosodium glutamate is controversial for its potential toxicity (Nahok et al, 2021) and more studies are needed to elucidate its effects on the human organism, this review will focus on clean label alternatives.…”
Section: Salt Replacersmentioning
confidence: 99%